2018
DOI: 10.1007/s11356-018-3781-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo exposure to tritium: a multi-biomarker approach using the fathead minnow, Pimephales promelas

Abstract: Highlights-Following a previously published field investigation, this study aims to characterize tritium effects on fish health under controlled conditions in a laboratory setting.-Fathead minnows were exposed to tritium activity concentrations up to 180,000 Bq/L.-At the highest levels of exposure, tritium increased DNA damage and modulated the immune responses.-Other markers were affected, including the neural system, oxidative stress and fatty acid composition.-No effects are reported on the measured health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Increase of ROS production was also shown for the different stressors, but not for all stages or all dose rates studied. These results confirm the known data on the effects of ionizing radiation in terms of oxidizing stress and genotoxicity , Gagnaire et al 2017, Gagnaire et al 2020b, Hu et al 2016.…”
Section: Comparison Of Results For Hto/tritiated Thymidine/gamma Radiation Exposuresupporting
confidence: 91%
See 1 more Smart Citation
“…Increase of ROS production was also shown for the different stressors, but not for all stages or all dose rates studied. These results confirm the known data on the effects of ionizing radiation in terms of oxidizing stress and genotoxicity , Gagnaire et al 2017, Gagnaire et al 2020b, Hu et al 2016.…”
Section: Comparison Of Results For Hto/tritiated Thymidine/gamma Radiation Exposuresupporting
confidence: 91%
“…The nervous system did not seem to be a target of HTO in zebrafish larvae, contrary to gamma irradiation. However, AChE activity was modified in adult fathead minnows exposed to HTO after depuration (Gagnaire et al 2020b). Moerover, genes involved in muscle contraction were modified by HTO (Arcanjo et al 2018), and swimming behavior of larvae was altered but only for one dose rate (Arcanjo et al 2020).…”
Section: Comparison Of Results For Hto/tritiated Thymidine/gamma Radiation Exposurementioning
confidence: 99%
“…Exchanges of HTO between water and organisms are rapid: maximal dose rates were obtained for 24‐h eggs. Several studies showed that tritium accumulated in adult organisms equilibrates with HTO concentration of the water and that the fraction of tritium bound to organic matter equilibrates with the concentration of HTO internalized (Galeriu and Melintescu ; Kim and Korolevych ; Melintescu et al ; Kim et al , ; Gagnaire et al , ). A companion paper study presented in detail the discussion about internalization results obtained after tritium contamination for 2 stages (24‐h eggs and 4‐dpf larvae) and 2 HTO concentrations (10 5 and 10 6 Bq/mL; Arcanjo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Exchanges of HTO between water and organisms are rapid: maximal dose rates were obtained for 24-h eggs. Several studies showed that tritium accumulated in adult organisms 7: Relative expression of genes (normalized to reference gene ef1) compared to control in larvae contaminated during 10 d at 10 4 , 10 5 , and 10 6 Bq/mL of tritiated water (n = 9) a 4 dpf 7 dpf 10 dpf 10 4 Bq/mL 10 5 Bq/mL 10 6 Bq/mL 10 4 Bq/mL 10 5 Bq/mL 10 6 Bq/mL 10 4 Bq/mL 10 5 Bq/mL 10 6 Bq/mL ache equilibrates with HTO concentration of the water and that the fraction of tritium bound to organic matter equilibrates with the concentration of HTO internalized (Galeriu and Melintescu 2011;Kim and Korolevych 2013;Melintescu et al 2015;Kim et al 2015Kim et al , 2019Gagnaire et al 2017Gagnaire et al , 2020. A companion paper study presented in detail the discussion about internalization results obtained after tritium contamination for 2 stages (24-h eggs and 4-dpf larvae) and 2 HTO concentrations (10 5 and 10 6 Bq/mL; Arcanjo et al 2019).…”
Section: Dose Rates Calculated For Htomentioning
confidence: 99%
“…The goal of this study was to adapt, optimize and validate the NBT assay (as described by [4] and [3] ) for use with kidney cells harvested from the fathead minnow ( Pimephales promelas ). To our knowledge, this assay has not yet been utilized to assess respiratory burst in this species, a common model for assessing general toxicity and emerging model in the field of immunotoxicity [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . This study explored the following experimental parameters to maximize the performance of the respiratory burst assay: 1) PMA concentration, 2) incubation time, 3) erythrocyte lysis, and 4) presence of superoxide dismutase (SOD).…”
Section: Methods Detailsmentioning
confidence: 99%